1968
DOI: 10.1126/science.159.3813.426
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Manufacture of Wooden Implements with Tools of Flaked Stone

Abstract: Several contemporary archeologists recaptutring an almost-lost art by developing skill at knapping (shaping) stone artifacts by pressure and percussion. However, little is known of how these artifacts could be used. We describe three experiments in the carving of wood implments with stone tools alone, and we outline some of the problems of making and applying a do-it- yolur-self lithic tool kit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Most experimental studies using stone flakes have concentrated on demonstrating plausible functions, from the manufacture of wooden implements (Crabtree and Davis, 1968), all the way up to the practicalities of butchering adult elephants (Frison, 1989;Schick and Toth, 1993). Recently, there appears to have been something of a reinvigoration of experimental approaches to lithic industries in a range of capacities, which evince a renewed emphasis on providing quantifiable results that may be examined within a statistical framework (Clarkson, 2002;Collins, 2008;Dewbury and Russell, 2007;Eren et al, 2008, in press;Hiscock and Clarkson, 2005;Jennings et al, 2010;Machin et al, 2007;Prasciunas, 2007;Shea et al, 2001;Shott et al, 2000;Stout et al, 2000;Toth et al, 2006).…”
Section: Experimental Framework For Stone Tool Use and Efficiency Asmentioning
confidence: 99%
“…Most experimental studies using stone flakes have concentrated on demonstrating plausible functions, from the manufacture of wooden implements (Crabtree and Davis, 1968), all the way up to the practicalities of butchering adult elephants (Frison, 1989;Schick and Toth, 1993). Recently, there appears to have been something of a reinvigoration of experimental approaches to lithic industries in a range of capacities, which evince a renewed emphasis on providing quantifiable results that may be examined within a statistical framework (Clarkson, 2002;Collins, 2008;Dewbury and Russell, 2007;Eren et al, 2008, in press;Hiscock and Clarkson, 2005;Jennings et al, 2010;Machin et al, 2007;Prasciunas, 2007;Shea et al, 2001;Shott et al, 2000;Stout et al, 2000;Toth et al, 2006).…”
Section: Experimental Framework For Stone Tool Use and Efficiency Asmentioning
confidence: 99%
“…This is unfortunate because it gives the impression that scientific components such as testing of hypotheses and controlling variables are not important in archaeological experiments (as discussed in e.g., Cunningham et al, 2008;Lammers-Keijsers, 2005;Mathieu, 2002;Outram, 2008;Reynolds, 1999). Such an impression undermines the important contributions that experimental studies following scientific procedures have made and continue to make, for example to the understanding of prehistoric production of food and tools and formation processes important to the archaeological record (see e.g., Coles, 1973;Crabtree & Butler, 1964;Crabtree & Davis, 1968;Gur-Arieh et al, 2012;Mallol et al, 2013a;Miller et al, 2010;Newcomer, 1971;Nielsen, 1991;Shea et al, 2001;Shipman et al, 1984). The fire experiments I conducted as part of my PhD project are 'actualistic' as described by Outram (2008, pp.…”
Section: Introduction To the Fire Experimentsmentioning
confidence: 99%
“…Evidence for metal tool use in a spear's manufacture requires definitive marks to be observed on its surface. Publications of experimental research comparing the use of stone and metal tools on wood are relatively rare (see for example Coutts 1977;Crabtree and Davis 1968). Coutts (1977:74) found that Polynesian steel adzes used to cut wood produced certain characteristic on the wooden surface that included a smooth finish and closely spaced precise lines whether incised or in relief.…”
Section: Detecting Traces Of Manufacturementioning
confidence: 99%